2021
DOI: 10.1073/pnas.2105276118
|View full text |Cite
|
Sign up to set email alerts
|

Visual exposure enhances stimulus encoding and persistence in primary cortex

Abstract: The brain adapts to the sensory environment. For example, simple sensory exposure can modify the response properties of early sensory neurons. How these changes affect the overall encoding and maintenance of stimulus information across neuronal populations remains unclear. We perform parallel recordings in the primary visual cortex of anesthetized cats and find that brief, repetitive exposure to structured visual stimuli enhances stimulus encoding by decreasing the selectivity and increasing the range of the n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 70 publications
4
14
0
Order By: Relevance
“…5B). Similar dynamic effects have been observed in the visual cortex in response to flashed stimuli [53], where this amplification of the input signal was hypothesized to be due to reverberating interactions among the nodes that eventually lead to the convergence towards a metastable stimulus-specific dynamic state. This state can be interpreted as the result of a highly parallelized search for the best match between sensory evidence and the priors installed by learning [2].…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…5B). Similar dynamic effects have been observed in the visual cortex in response to flashed stimuli [53], where this amplification of the input signal was hypothesized to be due to reverberating interactions among the nodes that eventually lead to the convergence towards a metastable stimulus-specific dynamic state. This state can be interpreted as the result of a highly parallelized search for the best match between sensory evidence and the priors installed by learning [2].…”
Section: Introductionsupporting
confidence: 54%
“…Thus, nodes activated by a particular stimulus become associated with one another by self-organizing interactions and form a cooperating, stimulusspecific assembly distinguished by synchronized and jointly enhanced responses. Such dynamics have also been observed in cortical networks [11, 53] and this has led to the binding by synchrony hypothesis (BBS) [29]. Moreover, such selective synchronization effects are to be expected if learning modifies recurrent connections according to a Hebbian correlation rule [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calcarine cortex and lingual gyrus are anatomical regions in the V1 that receive visual signals from the visual pathway, then transmit those signals to the higher visual cortex ( Beckmann et al, 2005 ). These rich dynamic properties exhibited by early visual neurons suggest that V1 does not encode the environment in a static manner; it exhibits rich spatial and temporal dynamic features ( Lazar et al, 2021 ). Huang et al (2018b) found that amplitude of low-frequency fluctuation values in the bilateral lingual gyrus were considerably lower in retinitis pigmentosa patients than in HCs.…”
Section: Discussionmentioning
confidence: 99%
“…Together, ON-responsive and OFF-responsive neurons play a key role in enabling better contrast sensitivity and rapid information transfer for both increments and decrements of light intensity ( Schiller et al, 1986 ). OFF responses are essential to indicate changes in visual scenes ( Bair et al, 2002 ), and are modulated by size and spatial frequency ( Jansen et al, 2019 ; Lazar et al, 2021 ), as well as contrast over a range of luminance ( Rahimi-Nasrabadi et al, 2021 ).…”
Section: Off Responses Across Sensory Modalitiesmentioning
confidence: 99%